A Compressed Identity: Self-Identification of Intellectual Muslim Women in Turkey. (13th November 2018) - Albayrak, H. Şule
Abstract : For decades the authoritarian secularist policies of the Turkish state, by imposing a headscarf ban at universities and in the civil service, excluded practising Muslim women from the public sphere until the reforms following 2010. However, Muslim women had continued to seek ways to increase their knowledge and improve their intellectual levels, not only as individuals, but also by establishing civil associations. As a result, a group of intellectual women has emerged who are not only educated in political, social, and economic issues, but who are also determined to attain their socio-economic and political rights. Those new actors in the Turkish public sphere are, however, concerned with being labeled as either "feminist, " "fundamentalist" or "Islamist." This article therefore analyzes the distance between the self-identifications of intellectual Muslim women and certain classifications imposed on them. Semi-structured in-depth interviews with thirteen Turkish intellectual Muslim women were carried out which reveal that they reject and critique overly facile labels due to their negative connotations while offering more complex insights into their perspectives on Muslim women, authority, and identity.